Insights into the Bacterial and Nitric Oxide-Induced Salt Tolerance in Sugarcane and Their Growth-Promoting Abilities - Anjney Sharma; Rajesh Kumar Singh; Pratiksha Singh; Anukool Vaishnav; Dao-Jun Guo; Krishan K. Verma; Dong-Ping Li; Xiu-Peng Song; Mukesh Kumar Malviya; Naeem Khan; Prakash Lakshmanan; Yang-Rui Li (Microorganisms, 2021)
Soil salinity causes severe environmental stress that affects agriculture production and food security throughout the world. Salt-tolerant plant-growth-promoting rhizobacteria (PGPR) and nitric oxide (NO), a distinctive signaling molecule, can synergistically assist in the alleviation of abiotic stresses and plant growth promotion, but the mechanism by which this happens is still not well known. In the present study, in a potential salt-tolerant rhizobacteria strain, ASN-1, growth up to 15% NaCl concentration was achieved with sugarcane rhizosphere soil. Based on 16S-rRNA gene sequencing analysis, the strain ASN-1 was identified as a Bacillus xiamenensis. Strain ASN-1 exhibits multiple plant-growth-promoting attributes, such as the production of indole-3-acetic acid, 1-aminocyclopropane-1-carboxylate deaminase, siderophores, HCN, ammonia, and exopolysaccharides as well as solubilized phosphate solubilization. Biofilm formation showed that NO enhanced the biofilm and root colonization capacity of the PGPR strain ASN-1 with host plants, evidenced by scanning electron microscopy. The greenhouse study showed that, among the different treatments, the combined application of PGPR and sodium nitroprusside (SNP) as an NO donor significantly (p ≤ 0.05) enhanced sugarcane plant growth by maintaining the relative water content, electrolyte leakage, gas exchange parameters, osmolytes, and Na+/K+ ratio. Furthermore, PGPR and SNP fertilization reduced the salinity-induced oxidative stress in plants by modulating the antioxidant enzyme activities and stress-related gene expression. Thus, it is believed that the acquisition of advanced information about the synergistic effect of salt-tolerant PGPR and NO fertilization will reduce the use of harmful chemicals and aid in eco-friendly sustainable agricultural production under salt stress conditions.